2012
DOI: 10.5194/angeo-30-991-2012
|View full text |Cite
|
Sign up to set email alerts
|

Variability of MLT winds and waves over mid-latitude during the 2000/2001 and 2009/2010 winter stratospheric sudden warming

Abstract: winter are examined to reveal the effects of stratospheric sudden warming (SSW) in mid-low-latitude MLT region. The result shows that the MLT daily zonal wind over these two sites reversed from eastward wind to westward wind for several days during the SSW events. The reversals were almost coincident with the polar stratospheric temperature reaching its maximum at 10 hPa, 90 • N and were about ten days prior to the reversal of high latitude stratospheric zonal wind at 10 hPa, 60 • N. The temporal variations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
3
7
0
Order By: Relevance
“…Therefore, the events studied here are exceptional even if they occur in a temporally short interval. Our observations of a continuous westward wind band from the pole to the subtropics and an occasionally stronger westward wind at mid-than at polar latitudes are corroborated by case studies of the SSW in 2010 by Chen et al (2012) Orsolini et al (2010). The aim of their paper was to show that mesospheric H 2 O and temperature measurements from the Odin satellite allow to distinguish between the formation of an elevated stratopause and the descent of dry mesospheric air into the polar stratosphere.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Therefore, the events studied here are exceptional even if they occur in a temporally short interval. Our observations of a continuous westward wind band from the pole to the subtropics and an occasionally stronger westward wind at mid-than at polar latitudes are corroborated by case studies of the SSW in 2010 by Chen et al (2012) Orsolini et al (2010). The aim of their paper was to show that mesospheric H 2 O and temperature measurements from the Odin satellite allow to distinguish between the formation of an elevated stratopause and the descent of dry mesospheric air into the polar stratosphere.…”
Section: Discussionsupporting
confidence: 61%
“…A more current event was studied by Stober et al (2012) where a stronger wind reversal was observed at mid-than at high latitudes during the SSW event of 2010. This mid-latitudinal wind reversal in 2010 was also observed in MF radar winds by Chen et al (2012) over Langfang (39 • N,166 • E). Fritz and Soules (1970) were the first who found temperature anomalies in the tropical stratosphere during the SSW of 1970 with the help of global satellite data.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Yuan et al (2012) found significant anomalies from climatological means with temperature anomalies as low as 30 K from climatological mean and zonal-mean wind turning eastward in the lower thermosphere in a reversal of climatological mean wind profile, which were directly attributed to the SSW. Chen et al (2012) reported changes in the wind structure during the SSW events of 2000over Wuhan (30 • N) and 2009 and found variability in wind responses at the two sites. also reported low and mid-latitude winds during the SSW events of 1998-1999, 2003-2004, and 2005-2006 found differences in the behavior of MLT winds at Tirunelveli (8.7 • N, 77.8 • E) and Collm (52 • N, 15 • E) and attributed the differences to variability in local gravity wave activity during the SSW events.…”
mentioning
confidence: 99%
“…Note that the tracing is performed in time-varying background conditions, not using the average fields shown in Figures 3c and 3d. The SSW in 2015 was a minor warming and 2010 was weak, too (Zülicke et al, 2018), even though the latter could have also been classified as major (Chen et al, 2012;Peters et al, 2014). Nevertheless, results suggest that GWs are able to propagate substantial meridional and zonal distances.…”
Section: Resultsmentioning
confidence: 90%